Determination of serum antibody titres and immune status of layer flocks against Newcastle Disease virus at Chittagong district of Bangladesh - Kashem, MA; Parvej, M; Hashem, MA; Moula, MM; Kibria, ASMG (International Journal of Natural Sciences, 2011)
A study was conducted to assess the level of serum antibody titres and immune status of layer birds against Newcastle Disease virus by Haemagglutination Inhibition (HI) test in different areas of Chittagong district during November to December, 2010. Sixteen layer flocks were selected based on different ages of birds. A total of 235 serum samples were collected and tested at Microbiology laboratory of CVASU. HI test was performed using commercial Newcastle Disease vaccine (Avinew®) as a source of 4HAU virus antigen. The antibody titre (GMT) levels in 18-26 weeks age group were found to be 70.198, followed by 47.551, 34.776, 17.281 and 18.855 in 27-40, 41-57, 58-73 and >73 weeks age groups, respectively. Moreover, 100% specific immunity against ND was found in 18-26, 27-40 and 41-57 weeks age groups of birds, whereas 93.33 and 94.73% specific immunity was found in 58-73 and >73 weeks age groups, respectively. On an average, 97.87% layer birds showed specific immunity and 2.13% showed nonspecific immunity against NDV. We considered HI titre of 1:8 or above as specific immunity and less than 1:8 as non specific immunity. Highest HI titre was found at the age of 18-26 weeks and lowest titre was at 58-73 weeks of age. The lower level of HI titre seemed to be directly related to some important factors relating to vaccination which have been highlighted in this paper. Key words: Antibody titers; Immune status; HI test; Newcastle disease virus; Layer birds. DOI: http://dx.doi.org/10.3329/ijns.v1i2.8818 International Journal of Natural Sciences (2011), 1(2):35-38